Developing river tourism products and the marketing strategies: observation and focus group discussion approach / Kai Xin Tay, Grace Ing Phang and Jennifer Kim Lian Chan - Kai, Xin Tay; Ing, Grace Phang; Kim, Jennifer Lian Chan (2023)
This study adopted a multi-stage and multi-method approach to identify the river tourism product development and related marketing strategies in Malaysia. Using Smith's (1994) tourism product model, the study aimed to examine how all five elements of the model contribute to the development of river tourism products. The study utilised an inductive approach, incorporating observation and focus group discussions (FGDs) to explore the development of the Putatan-Petagas River tourism product and its marketing strategies. The analysis revealed five themes, categorised into six sections, with physical plants having two sections, including resources and potential areas for river tourism product development, service, hospitality, freedom of choice, and involvement. The findings provide a robust examination of TPD and marketing strategies for river tourism products and highlight the importance of considering all elements of the tourism product model for success. This study offers insights into the development and marketing of river tourism products, which can assist in the planning and promotion of sustainable tourism in Malaysia.